Pengaruh Pola Pendidikan Kewirausahaan dan Pengalaman Berwirausaha Masyarakat terhadap Kesiapan Pendirian Kampung Edukasi Desa Kemiri - Heny Kusdiyanti; Indra Febrianto; Robby Wijaya; Nur Indah Agustina (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This article aims to examine the effect of the pattern of economic education and community entrepreneurship experience on the readiness to establish an educational village in Kemiri Village. The approach used in this study is quantitative explanation using primary data collected from questionnaires with a total of 114 respondents consisting of four hamlets in Kemiri Village using purposive random sampling method. Data analysis used is classical assumption test, coefficient of determination test, partial test (t test) and simultaneous test (F test). The results of this study indicate that partially and simultaneously the pattern of economic education and community entrepreneurship experience has a significant positive effect on the readiness to establish an educational village in Kemiri Village. This finding also confirms the existence of the theory of involvement and the theory of connectionalism which also applies in explaining the readiness to establish an educational village. The experience of community entrepreneurship is strengthened by the existence of local wisdom which is the potential in Kemiri Village to initiate new businesses or develop existing businesses. This will contribute better if it is collaborated with the pattern of economic education that the Kemiri Village community gets. Abstrak: Artikel ini bertujuan untuk melihat pengaruh pola pendidikan ekonomi dan pengalaman berwirausaha masyarakat terhadap kesiapan pendirian kampung edukasi di Desa Kemiri. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif eksplanasi dengan menggunakan data primer yang dikumpulkan dari kuisioner dengan jumlah responden 114 yang terdiri dari empat dusun di Desa Kemiri dengan menggunakan metode purposive random sampling. Analisis data yang digunakan adalah pengujian asumsi klasik, uji koefisien determinasi, uji parsial (uji t) dan uji simultan (uji F). Hasil penelitian ini menunjukkan bahwa secara parsial maupun simultan pola pendidikan ekonomi dan pengalaman berwirausaha masyarakat berpengaruh positif signifikan terhadap kesiapan pendirian kampung edukasi di Desa Kemiri. Temuan ini sekaligus mengkonfirmasi adanya teori keterlibatan dan teori koneksionalisme yang juga berlaku dalam menjelaskan kesiapan pendirian kampung edukasi. Pengalaman berwirausaha masyarakat diperkuat dari adanya local wisdom yang menjadi potensi di Desa Kemiri untuk menginisiasi usaha baru ataupun pengembangan usaha yang sudah ada. Hal ini akan berkontribusi lebih baik jika dikolaborasikan dengan pola pendidikan ekonomi yang di dapatkan masyarakat Desa Kemiri.